2004
DOI: 10.1055/s-2004-869591
|View full text |Cite
|
Sign up to set email alerts
|

Statins Effect on Smooth Muscle Cell Proliferation

Abstract: Clinical trials have firmly established that 3-hydroxy-3-methylglutaryl-coenzyme-A reductase inhibitors (statins) can induce regression of vascular atherosclerosis as well as reduction of cardiovascular-related morbidity and death in patients with and without coronary artery disease. These beneficial effects of statins are usually assumed to result from their ability to reduce cholesterol synthesis. However, because mevalonic acid is the precursor not only of cholesterol but also of many nonsteroidal isoprenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Specifically relevant to GA, statins were reported to selectively inhibit several pro-inflammatory mediators including interleukin (IL)-2, IL-12, interferon (IFN)-γ, tumor necrosis factor-α, as well as a number of chemokines, adhesion molecules, co-stimulatory molecules and transcription factors (9). Additionally, an association between statins and reduction of endothelial dysfunction (10) and VSMC proliferation (11), both potentially important to the pathobiology of GA, has also been suggested. Also, the incidence of coronary allograft vasculopathy after heart transplantation was reduced (12), and improved functional outcomes after kidney transplantation were reported in association with statin administration (13).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically relevant to GA, statins were reported to selectively inhibit several pro-inflammatory mediators including interleukin (IL)-2, IL-12, interferon (IFN)-γ, tumor necrosis factor-α, as well as a number of chemokines, adhesion molecules, co-stimulatory molecules and transcription factors (9). Additionally, an association between statins and reduction of endothelial dysfunction (10) and VSMC proliferation (11), both potentially important to the pathobiology of GA, has also been suggested. Also, the incidence of coronary allograft vasculopathy after heart transplantation was reduced (12), and improved functional outcomes after kidney transplantation were reported in association with statin administration (13).…”
Section: Introductionmentioning
confidence: 99%
“…Known PK parameters for statin therapy were taken from package inserts and the literature. 19,20 We included known mechanisms of action for statins, ezetimibe, and fibrates into the model and calibrated the parameters influencing the pharmacodynamic effect of each drug to the average clinical response across clinical trial data reported in the literature. 5,2024 …”
Section: Model Calibration and Resultsmentioning
confidence: 99%
“…Simvastatin was chosen because of the known antioxidant effect of this drug group (10), and the effect of statins on muscle cell metabolism (within the vascular system) has been well characterized (2). It has been shown that simvastatin increases the expression of two DNA repair proteins, MLH1 and XRCC1; thus MSH2 suppression by simvastatin is likely to be a very specific and not a general phenomena in the repair system (37).…”
Section: Discussionmentioning
confidence: 99%